L’aide aux apprentissages : le cas des collégiens avec un trouble du spectre de l’autisme et de leurs enseignants - Sabine Zorn; Minna Puustinen (Recherches en Éducation)
With the February 11, 2005, law for equality of rights and opportunities, participation and citizenship of people with disabilities, the question of help to students with disabilities has become a central issue in France. Within this context, and with the aim of contributing to improving the learning conditions of secondary students with an autism spectrum disorder (ASD), lower secondary teachers and students with ASD were interviewed. We analyzed both (1) help provided to lower secondary students with ASD by teachers, and (2) help sought by lower secondary students with ASD from teachers in the classroom. The results showed that teachers mainly provided their students with ASD with generic (rather than specific) help and that most students with ASD actively sought help in the classroom.